Effects of a treatment with Se‐rich rice flour high in resistant starch on enteric dysbiosis and chronic inflammation in diabetic ICR mice. (4th October 2016) - Yuan, Huaibo; Wang, Wenjuan; Chen, Deyi; Zhu, Xiping; Meng, Lina
Abstract: BACKGROUND: Enteric dysbiosis is associated with chronic inflammation and interacts with obesity and insulin resistance. Obesity and diabetes are induced in ICR (Institute of Cancer Research) mice fed a high‐fat diet and administered a streptozocin injection. These mice were treated with normal rice (NR), normal rice with a high resistant starch content (NRRS) or Se‐rich rice (selenium‐enriched rice) with a high resistant starch content (SRRS). RESULTS: Faecal cell counts of Bifidobacterium, Lactobacillus and Enterococcus were significantly higher in SRRS‐treated mice than in diabetic controls, while Enterobacter cloacae were lower. Similar results were also found in NRRS‐treated mice. In contrast, no significant difference was found between NR‐treated and diabetic control groups. The treatments with SRRS and NRRS reduced the faecal pH values of the diabetic mice. Regarding the inflammatory factor levels, lower levels of serum C‐reactive protein (CRP), tumour necrosis factor‐α (TNF‐α), interleukin‐6 (IL‐6), nuclear factor‐k‐gene binding (NF‐κB) and leptin (LEP) and higher adiponutrin (ADPN) levels were found in the SRRS and NRRS‐treated mice compared with the diabetic and NR‐treated mice. In addition, the CRP, IL‐6 and NF‐κB levels in the SRRS‐treated mice were significantly reduced compared with those observed in the NRRS‐treated mice. The reverse transcription‐PCR (RT‐PCR) results showed that the SRRS and NRRS‐treated mice presented higher expression levels of orphan G protein‐coupled receptor 41 (GPR41) and orphan G protein‐coupled receptor 43 (GPR43) proteins compared with diabetic mice and NR‐treated mice. CONCLUSION: These results indicate that treatments with rice high in RS exert beneficial effects by improving enteric dysbiosis and chronic inflammation. In addition, selenium and RS may exert synergistic effects on chronic inflammation. © 2016 Society of Chemical Industry